2001
DOI: 10.1046/j.1365-2168.2001.01659.x
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin and octreotide in the prevention of postoperative pancreatic complications and the treatment of enterocutaneous pancreatic fistulas: a systematic review of randomized controlled trials

Abstract: There was major disagreement between the studies on whether use of the drugs in question is of value in preventing postoperative complications. This analysis suggests that, in units where the postoperative fistula rate following pancreaticoduodenectomy for neoplasia and other pancreatic conditions exceeds 10 per cent, somatostatin or octreotide administered before operation may significantly reduce the rate of major postoperative complications, particularly pancreatic fistulas. The identified evidence also sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
12

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(75 citation statements)
references
References 33 publications
3
60
0
12
Order By: Relevance
“…The rationale for its use is to reduce the risk of pancreatic anastomotic fistulas by decreasing the volume of pancreatic exocrine secretions. Several RCTs have resulted in four systemic reviews and meta-analyses that assessed the possible role of a protective effect in pancreatic surgery [163][164][165][166]. The most recent meta-analysis involved 17 trials with 1,457 patients undergoing PD and 686 undergoing distal or other resections [166].…”
Section: Somatostatin Analoguesmentioning
confidence: 99%
“…The rationale for its use is to reduce the risk of pancreatic anastomotic fistulas by decreasing the volume of pancreatic exocrine secretions. Several RCTs have resulted in four systemic reviews and meta-analyses that assessed the possible role of a protective effect in pancreatic surgery [163][164][165][166]. The most recent meta-analysis involved 17 trials with 1,457 patients undergoing PD and 686 undergoing distal or other resections [166].…”
Section: Somatostatin Analoguesmentioning
confidence: 99%
“…Az elhúzódó, rendszerint hat hónapig tartó konzervatív kezelés az esetek 80%-ában a fi stula záródá-sához vezet. Kiterjedt konzervatív kezelésre refrakter esetekben a fi stula sebészi zárására van szükség [21,22,23].…”
Section: Hasnyálmirigysipolyokunclassified
“…Az eredmények arra utalnak, hogy octreotiddal az egyéb kezeléssel eredményesen nem befolyásolható, állandósult, nagy hozamú külső hasnyálmirigysipolyok gyógyulása elősegít-hető [24,25]. A hazai és nemzetközi adatok és a nagy metaanalízisek szerint a perioperatív szomatosztatinanalóg a műtétek után keletkező sipolyok arányát is csök-kenti [22,25,26,27,28,29,30,31,32,33].…”
Section: Hasnyálmirigysipolyokunclassified
See 1 more Smart Citation
“…30 Though some studies documented significant reduction in fistula output, most studies to date have not shown higher fistula closure rate or shortened fistula closure time. [31][32][33][34][35][36][37][38][39][40] Data in these and other studies are confounded by the small numbers of patients included, inclusion of a large proportion of patients with pancreatic fistulas together with patients with enterocutaneous fistula, and heterogeneity within the patient cohorts studied. Data concerning the relative efficacy of one drug over another are also limited.…”
Section: Controlling Fistula Outputmentioning
confidence: 99%